RESEPSI ESTETIS H.B. JASSIN TERHADAP AYAT METAFORA DALAM BINGKAI TEORI KRITIK SASTRA - Muttaqin, Ahmad (Lajnah Pentashihan Mushaf Al-Qur'an, 2017)
It is of interest to point out that Alquranul Karim Bacaan Mulia (AKBM) has two sides, or regarded as dualism. One side is as quranic translation and the other hand, made in poetrical form. Some papers have discussed AKBM by using the theory of translation an sich. Hence, this aims to analyze how HB Jassin’s aesthetic reception to metaphorical quranic verses by other approach. Using the theory of literary criticism, it concludes that, first, HB Jassin gave a deep and beautiful meaning of translation of metaphorical verses by poetical way. Second, to study AKBM needs not only theory of translation, but also theory of literary. Keywords: AKBM, Metaphorical Verses, Literary Criticism